2007
DOI: 10.1080/03323310701296193
|View full text |Cite
|
Sign up to set email alerts
|

Student discourse on physical activity and sport among Irish young people

Abstract: This article explores accounts of student discourse related to the role of physical activity and sport in the lives of Irish children and youth. The data source is a purposeful sample of student narratives based upon age of student, type of school and gender, and sought representation from both rural and urban settings. Data were derived from an original, random sample of approximately 4,100 texts written by Irish young people (ages 10Á12 and 14Á17). Data suggest sport plays a pervasive role in the lives of Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, the dominance of team games suggest that physical education has not responded to the diversification of young people's wider physical culture as reflected by what they like to do (Collier et al, 2007). This reflects other contexts such as Australia, where Garrett and Wrench (2007) found that early school based experiences of pre-service teachers were dominated by sport-related discourses.…”
Section: Coulter and D Ní Chróinínmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the dominance of team games suggest that physical education has not responded to the diversification of young people's wider physical culture as reflected by what they like to do (Collier et al, 2007). This reflects other contexts such as Australia, where Garrett and Wrench (2007) found that early school based experiences of pre-service teachers were dominated by sport-related discourses.…”
Section: Coulter and D Ní Chróinínmentioning
confidence: 95%
“…The process of engagement in sport and physical activities by young people is complex and the larger cultural and social context must be taken into account when devising sporting and physical activity opportunities for young people reflecting 'the changing times and unique interests of young people' (Collier et al, 2007).…”
Section: Physical Culture In Irelandmentioning
confidence: 99%
“…The number of movement culture references within these young people's narratives was limited in comparison with our previous analysis of narratives from primary-aged students Lifestyles and gendered patterns of leisure and sporting interests among Irish adolescents 29 (Collier et al, 2007). However, the narratives reported here do convey the complex and diverse cultural contexts in which young people engage with sport and physical activity.…”
Section: Resultsmentioning
confidence: 75%
“…In an earlier paper (Collier, MacPhail & O'Sullivan, 2007), we explored the accounts of student discourse related to the role of physical activity and sport in the lives of Irish children and youth.…”
Section: Introductionmentioning
confidence: 99%
“…Within the physical culture arena, there are a growing number of examples in which young people’s own ideas and understandings of the ways they engage with physical culture – the ways they play, exercise, move, and (dis)engage in activity practices (Azzarito and Kirk, 2013; O’Sullivan and MacPhail, 2010) – have been explored. Studies that have sought young people’s views have investigated such topics as: the role and significance of physical activity in the lives of young people (Collier et al, 2007; MacPhail et al, 2009); the negotiation and construction of physical education curricula (e.g. Enright and O’Sullivan, 2010; Oliver et al, 2009); the meanings children assign to physical activity (Patton and Parker, 2013); physical education experiences from the young person’s perspective (e.g.…”
Section: Introductionmentioning
confidence: 99%